(untitled) (Jurnal Fenomena Kesehatan, 2025)
Stunting or chronic malnutrition is another form of growth failure that arises as a result of long-standing malnutrition. This study aims to determine the relationship between family economic level and the incidence of stunting in Long Ikis District, Paser Regency in 2022. This research is a quantitative type through a cross sectional approach with the sampling technique used is non-probability sampling with purposive sampling type with a total sample of 49 people. The results showed that respondents with a family economic level relationship with the incidence of stunting showed that respondents with a low economy were 1 person (2.0%) with good knowledge of stunting 0 and with less knowledge of stunting as many as 1 person (2.0%), while respondents with moderate economy as many as 31 people (63.3%) with good knowledge of stunting 26 people (53.1%) and with less knowledge of stunting 5 people (10.2%). And in the high economy as many as 17 people (34.7%) with good knowledge of stunting as many as 15 people (30.7%) and with less knowledge of stunting 2 people (4.1%). The results of the Chi-Square test showed that there was no relationship between family economic level and the incidence of stunting in Long Ikis District, Paser Regency with p = 0.068 <a = 0.05. To prevent an increase in the prevalence of stunting, treatment is needed starting early, such as good parenting and the need for monitoring the growth of toddlers with regular height measurements through posyandu, and regular health education is needed to increase nutritional knowledge for parents, especially mother’s knowledge so that knowledge is needed. increased in order to create a family that is aware of nutrition.